KOMUNIKASI SEBAGAI WUJUD KOMPETENSI SOSIAL GURU DI SEKOLAH - Muhammad Aswar Ahmad (Ilmu Komunikasi UIN Alauddin Makassar, 2019)
Social competence is one of the four mandatory competencies that teachers must possess. Basically this competency is one of the things that is very supportive in learning, both inside and outside the classroom. Teacher social competence is an effective communication skill to students, peers, school staff, and the environment in which the teacher lives. The core of social competence is the skill to build effective communication through the establishment of good social relations to all school stakeholders intended at the outset. Based on these competencies, teachers are expected to become figures that can directly motivate students to learn or become figures that are always looked forward to in face-to-face meetings in class. Communication is the main key to the practice of social competence; there are several communication principles that are expected to exist to maximize the practice. These principles are; respect (respect), empathy (empathy), clear in speaking (audible), what is conveyed can be understood (clarity), and communication must be built with the principle of modesty (humble).